Las corrientes políticas del Partido de la Revolución Democrática en el Distrito Federal (1997-2012) - Cruz Arzate, Carlos (El Colegio de México A.C., 2017)
The militants of the Party of the Democratic Revolution have organized themselves in political currents in what is now officially called Mexico City with a view to winning the largest number of partisan positions, which are necessary to obtain different economic and political resources such as the candidacies for the local councils, the borough heads and the various public positions within the Government of the Federal District. In spite of the diversity of factions within the PRD in the capital city, a dominant coalition has been formed by some of these in order to remain the leading political force in the country’s capital.